MENINGKATKAN KESADARAN MENJAGA KEBERSIHAN LINGKUNGAN MELALUI SOSIALISASI FILM CITARUM - Elvy Maria Manurung; Sukawarsini Djelantik; Adelbertus Irawan J. H (Jurnal Abdimas Bina Bangsa, 2023)
Industrialization on the one hand has opened up a large number of job opportunities but on the other hand, it has led to pollution which is very dangerous for life. The tragedy of the Citarum River as the dirtiest river in the world in 2018 became one of the milestones of the Citarum Harum Program's launching. This community service activity has been carried out from 2019 until 2022, focusing on building awareness regarding the importance of maintaining cleanliness in the community surrounding the Citarum River through socializing movies that won the Citarum Movie Award competition by UNPAR in 2019. Six schools and one community near Citarum River were visited and invited to discuss how to keep the environment especially Citarum River clean, after watching screenings of Citarum Movie Winner. The results of this Community Service show a positive impact in building public awareness about environmental cleanliness. Some schools that have been visited even started to apply the 3R Principles (reduce-reuse-recycle) and make recycled products from plastic waste that are useful and generate income